2021
DOI: 10.1038/s41390-021-01545-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory syndrome in COVID-19–SISCoV study: systematic review and meta-analysis

Abstract: BACKGROUND: There has been a recent upsurge in the cases of Multisystem inflammatory syndrome in children (MIS-C) associated with Coronavirus disease . We performed a systematic review and meta-analysis on the demographic profile, clinical characteristics, complications, management, and prognosis of this emerging novel entity. METHODS: Using a predefined search strategy incorporating MeSH terms and keywords, all known literature databases were searched up till 10th July 2020. The review was done in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 81 publications
2
46
0
5
Order By: Relevance
“… 9 , 17 The mortality of 5% ( N = 2) in this index study is higher than that reported from developed countries. 3 8 Both cases died because of refractory shock within 24 hours of admission. This highlights the importance of early identification, resuscitation (with fluids and vasoactive drugs), and targeted immunomodulation upon first contact with the healthcare facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 17 The mortality of 5% ( N = 2) in this index study is higher than that reported from developed countries. 3 8 Both cases died because of refractory shock within 24 hours of admission. This highlights the importance of early identification, resuscitation (with fluids and vasoactive drugs), and targeted immunomodulation upon first contact with the healthcare facility.…”
Section: Discussionmentioning
confidence: 99%
“… 3 7 With supportive treatment and immunomodulation (intravenous immunoglobulin [IVIG] and steroids), the short-term outcome is good and mortality is 0–2%. 3 8 Long-term treatment with glucocorticoids, aspirin, or anticoagulants in MIS-C is based on experience with other inflammatory conditions like Kawasaki disease (KD) and the exact duration of treatment is not known. The suggested duration for immunomodulation is 2–3 weeks or even longer with severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…3.Alterações de extremidades (eritema palmar ou plantar, edema de mãos e pés, descamação periungueal na fase convalescente). Figura 1 -Mecanismos patogênicos hipotéticos para a SIMS, sumário (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). SARS-CoV-2, coronavirus 2 da síndrome respiratória aguda grave; SIMS, síndrome inflamatória multisistêmica; Th1, célula T helper 1; Th17, célula T helper 17.…”
Section: Síndrome De Inflamação Multissistêmica E Doença De Kawasakiunclassified
“… 3 A recent meta-analysis found that gastrointestinal involvement was present in 84.3% of MIS-C cases. 4 In New York State, between 1 March and 10 May 2020, the incidence of MIS-C in those younger than 21 years was 2 per 100,000. 3 We describe an MIS-C patient whose initial presentation resembled appendicitis.…”
Section: Introductionmentioning
confidence: 99%